2013
DOI: 10.1007/s00127-013-0754-3
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and support in first-episode psychosis: exploring the role of loneliness and anxiety

Abstract: PURPOSE-To investigate social support and network features in people with first episode psychosis, and to examine anxiety as a possible mediator between loneliness and a rating of paranoia.METHOD-Thirty eight people with first-episode psychosis were recruited for a cross-sectional study. Self report questionnaires and structured interviews assessed symptoms, functioning, and qualitative social network and support features. A mood-induction task involved watching anxiety-inducing pictures on a computer screen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
84
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 45 publications
(75 reference statements)
15
84
1
3
Order By: Relevance
“…In a sample of Swedish army members, premorbid assessments showed that preferring to socialize in small groups, having fewer than two friends, and not having a girlfriend were associated with an increased risk of developing schizophrenia (Malmberg et al, 1998). Another study of individuals with first episode psychosis found that many individuals reported poor perceived social support and feeling lonely several days a week (Sündermann et al, 2014). Many of these individuals did not have even one confidant, which was associated with being more susceptible to loneliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of Swedish army members, premorbid assessments showed that preferring to socialize in small groups, having fewer than two friends, and not having a girlfriend were associated with an increased risk of developing schizophrenia (Malmberg et al, 1998). Another study of individuals with first episode psychosis found that many individuals reported poor perceived social support and feeling lonely several days a week (Sündermann et al, 2014). Many of these individuals did not have even one confidant, which was associated with being more susceptible to loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the study aimed to evaluate potential differences between UHR individuals and controls in number of close friends, social network diversity, perceived social support, quality of relationships with family and friends, and loneliness. Based on findings from past studies of individuals with psychosis, we hypothesized that compared to healthy controls, UHR participants would report significantly fewer close friends (Dickey et al, 2005), less social network diversity (Goldberg et al, 2003), less perceived social support (Pruessner et al, 2011), poorer quality relationships with family and friends (Cohen and Iii, 2009), and more loneliness (Sündermann et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, increased levels of perceived social support have been linked to an absence of psychotic experiences amongst adolescents at high risk due to exposure to multiple forms of victimisation (poly-victimised) [4]. Research has suggested that social support may buffer the effects of stress [58], improve self-esteem [911], and reduce feelings of loneliness [12,13], which may all protect against psychotic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…; Sündermann et al . ). She was admitted to the Darlinghurst Reception House 4 weeks before the birth of the child because she was reported as being dull and disinterested, emotional, and destructive, and was treated with sedation.…”
Section: Discussionmentioning
confidence: 97%